Faculty Council Meetings - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
Two Faculty Council Meetings were conducted on 13th May 2016 and 05th August 2016, to approve and acknowledge paperwork on Academic Matters, Research & Post Graduate Matters and Administrative Affairs.